Students' Perceptions of Kahoot in Learning: A Study of Fifth-Semester Islamic Education Students - Ramdhano, Yanri (Institut Agama Islam Al-Quran Al-Ittifaqiah (IAIQI) Indralaya, 2025)
This study explores the perceptions of Islamic Education students at UIN Sulthan Thaha Saifuddin Jambi regarding the use of the Kahoot application in Islamic Religious Education. Using qualitative methods, data were collected through open-ended questionnaires from 15 students. The findings reveal that most students viewed Kahoot positively, appreciating its engaging and interactive nature, which enhanced their understanding of the material. The gamification aspect of Kahoot was seen as a motivating factor that made learning more enjoyable. However, some students raised concerns about technical difficulties and time constraints during the game sessions. The study concludes that Kahoot can be an effective tool to boost student engagement and motivation in learning Islamic Religious Education, but it requires further adaptation to address technical challenges and optimize learning outcomes. This research contributes to the literature by demonstrating that Kahoot not only functions as an assessment tool but also as a means to increase student interaction and learning motivation in the context of Islamic Religious Education.